Research on the Networking Strategy in Indoor Visible Light Communication - Yang Liu; Hua Zhao; Kaizhi Huang; Xinsheng Ji (Dianxin kexue)
The correlation studies mainly focus on the fields of elements design, physical layer communication, system planning and design on VLC network have not obtained enough attention yet. Therefore, the technical features of VLC and the typical network architecture were discussed, according to the evolution and development trend of the wireless communication system, some networking strategies for the indoor visible light networking were proposed, such as hierarchical cell coverage, control plane and user plane separation, distributed model and client-server model coexist in strategy. The key technologies of VLC system about the layout of lighting, network handover and access control were analyzed.